2023
DOI: 10.1097/qad.0000000000003628
|View full text |Cite
|
Sign up to set email alerts
|

Systematic review and quantitative and qualitative comparative analysis of interventions to address HIV-related stigma and discrimination

Abstract: A strong global commitment exists to eliminate HIV-related stigma and discrimination, and multiple strategies to reduce or eliminate stigma and discrimination have been tried. Using a PICOTS framework and applying the Grading of Recommendations, Assessment, Development, and Evaluation (GRADE) criteria, we undertook a systematic review to determine the success of interventions aiming to address internalized stigma, stigma and discrimination in healthcare, and at the legal or policy level, and to identify their … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 85 publications
(110 reference statements)
0
7
0
Order By: Relevance
“…Since HIV-related stigma, in its different manifestations, has been identified as a threat to the global response to the HIV epidemic [ 14 , 25 , 26 ], several interventions have been developed and tested to address it. A recent systematic review, in which 70 articles were evaluated, indicated different fronts for confronting HIV-related stigma [ 52 ]. The most-tested measures aimed at treating the harmful effects associated with stigma include tailored interventions to manage internalized homophobia, which usually shows a bidirectional relationship with HIV-related stigma.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Since HIV-related stigma, in its different manifestations, has been identified as a threat to the global response to the HIV epidemic [ 14 , 25 , 26 ], several interventions have been developed and tested to address it. A recent systematic review, in which 70 articles were evaluated, indicated different fronts for confronting HIV-related stigma [ 52 ]. The most-tested measures aimed at treating the harmful effects associated with stigma include tailored interventions to manage internalized homophobia, which usually shows a bidirectional relationship with HIV-related stigma.…”
Section: Discussionmentioning
confidence: 99%
“…Interventions in this area mostly involve the creation of support groups for people living with HIV, respecting sociodemographic specificities and those related to other possible additional stigmas, such as sexual stigma, racism, and ageism [ 52 ]. Meetings typically occur weekly, for several months, and are led by trained facilitators or mental health professionals.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations